2015
DOI: 10.1128/aem.04066-14
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation Improves Microbial Salinity Resistance and Organofluorine Removal in Bioelectrochemical Systems

Abstract: cFed batch bioelectrochemical systems (BESs) based on electrical stimulation were used to treat p-fluoronitrobenzene (p-FNB) wastewater at high salinities. At a NaCl concentration of 40 g/liter, p-FNB was removed 100% in 96 h in the BES, whereas in the biotic control (BC) (absence of current), p-FNB removal was only 10%. By increasing NaCl concentrations from 0 g/liter to 40 g/liter, defluorination efficiency decreased around 40% in the BES, and in the BC it was completely ceased. p-FNB was mineralized by 30% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…S8). The pitting corrosion potential after the surface heat treatment in H2 increased to 0.35 V (vs. Ag/AgCl), which is higher than that of stainless steel (0.2 V) [22]. This result confirmed that biocorrosion did not occur in the anodic environment and that TNA-H2 has sufficiently high corrosion resistance for use as an anode in MFCs.…”
Section: Electrochemical Characteristicsmentioning
confidence: 53%
See 1 more Smart Citation
“…S8). The pitting corrosion potential after the surface heat treatment in H2 increased to 0.35 V (vs. Ag/AgCl), which is higher than that of stainless steel (0.2 V) [22]. This result confirmed that biocorrosion did not occur in the anodic environment and that TNA-H2 has sufficiently high corrosion resistance for use as an anode in MFCs.…”
Section: Electrochemical Characteristicsmentioning
confidence: 53%
“…All the reactor configurations and operating temperatures were the same as those applied in our previous study [11]. The anolyte consisted of modified M9 medium [22] with 1 g/L sodium acetate as the electron donor and a 10-mL inoculation of fresh anodic effluent from an existing parent MFC reactor. The catholyte consisted of 20 g/L potassium ferricyanide.…”
Section: Mfc Operationmentioning
confidence: 99%
“…Moreover, biocathode displayed higher pollutants reduction efficiency and selectivity, lower reduction overpotentials than those of the abiotic cathodes (Liang et al, 2013Wang et al, 2011). The electrical stimulation could also simultaneously improve the salinity resistance and halogenated nitroaromatics removal efficiency in biocathode communities (Feng et al, 2015). Additionally, a previous study revealed that the catalytic activity of ambient temperature acclimatized CAP-degrading biocathode was obviously decreased when the temperature dropped from 25 C to a low temperature 10 C .…”
Section: Introductionmentioning
confidence: 99%
“…Bioelectrochemical system (BES) has been developed for the cathodic reduction of various organic pollutants including nitroaromatics, azo dyes, halogenated aromatics, alkanes and ethylenes (Feng et al, 2015;Liang et al, 2014;Mu et al, 2009;Radjenovic et al, 2012;Shen et al, 2013;Strycharz et al, 2008Strycharz et al, , 2010Wang et al, 2011). Recently, antibiotics such as chloramphenicol (CAP), florfenicol, metronidazole, nitrofurazone and furazolidone, which are widely used in China, could be effectively reduced to antibacterial inactivity products with abiotic cathode or biocathode (Kong et al, 2015a(Kong et al, , 2015bLiang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bioelectrochemical systems (BES), employing electrochemically active microorganisms to catalyze oxidative or reductive reactions in the anode or cathode respectively, have attracted a considerable amount of attentions in recent decades (Pandey et al, 2016;Pant et al, 2010;Wang et al, 2015;Yun et al, 2017a), especially its merits on the bioelectrodegradation of various organic pollutants including nitro-, azo-, halo-aromatics and antimicrobial agents based on the microbial electrode-respiration process (Cui et al, 2014Feng et al, 2015;Gao et al, 2016;Jiang et al, 2016a;Li et al, 2016;Liang et al, 2013;Sun et al, 2013;Wang et al, 2011Wang et al, , 2016Zhang et al, 2017). Generally, operational factors could impact the catalytic efficiency and functioning stability of abiotic cathode/biocathode reactors (e.g.…”
Section: Introductionmentioning
confidence: 99%